2012
DOI: 10.1088/0256-307x/29/1/014601
|View full text |Cite
|
Sign up to set email alerts
|

Shedding Phenomenon of Ventilated Partial Cavitation around an Underwater Projectile

Abstract: A new shedding phenomenon of ventilated partial cavitations is observed around an axisymmetric projectile in a horizontal launching experiment. The experiment system is established based on SHPB launching and high speed photography. A numerical simulation is carried out based on the homogeneous mixture approach, and its predicted evolutions of cavities are compared with the experimental results. The cavity breaks off by the interaction between the gas injection and the re-entry jet at the middle location of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Once the local pressure in the liquid falls below its saturated vapor pressure, an evaporation process starts, with the gas nuclei in the liquid being developed, to form the so-called cavitating flow [7] . The cavitation is normally accompanied by several undesirable consequences, such as the noise [8] , the vibrations [9] , the destruction of structures [10] , the loss of efficiency and material [11][12] .…”
Section: Introduction mentioning
confidence: 99%
“…Once the local pressure in the liquid falls below its saturated vapor pressure, an evaporation process starts, with the gas nuclei in the liquid being developed, to form the so-called cavitating flow [7] . The cavitation is normally accompanied by several undesirable consequences, such as the noise [8] , the vibrations [9] , the destruction of structures [10] , the loss of efficiency and material [11][12] .…”
Section: Introduction mentioning
confidence: 99%
“…Wang determined the relationship between the speed and position of a re-entry jet and adverse pressure gradient. The results of these studies can be used to predict the speed and cavity length of re-entry jets [30].…”
Section: Introductionmentioning
confidence: 99%
“…Pham et al 15 performed air injection in the suction side of a hydrofoil to suppress re-entrant flow, and it is found that the unsteadiness of cavitating flow is reduced. Wang et al 16 performed air injection in the unsteady cavitating flows around underwater vehicle, and the influence of air injection on cavity collapse is investigated. Yu et al 17 found that the unsteadiness of cavitating flow is adjusted due to the interaction between air and re-entrant flow.…”
Section: Introductionmentioning
confidence: 99%